The Effect of Exchange Rate, Jakarta Islamic Index (JII) and Indonesian Sharia Bank Certificate (SBIS) on Islamic Mutual Funds Growth with Inflation as a Moderate Variable - Musalim Ridlo; Tri Yunianto; Imania Anisya Rohmah (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
This study aims to analyze the influence of exchange rate, Jakarta Islamic Index, Indonesian Shari Bank Certificate towards the growth of Islamic mutual funds with Inflation as a moderate variable in Indonesia period 2014-2018. This study uses a quantitative approach using a secondary data type with time series model. Furthermore, the data were tested using multiple linear regression models and moderated regression analysis (MRA) through EVIEWS 9 statistical application. The results of this study indicate that the variable exchange rate has a significant negative effect on the growth of Islamic mutual funds, Jakarta Islamic index has a significant positive effect, inflation has no significant negative effect, and Indonesian sharia bank certificate has no significant effect on the growth of Islamic mutual funds. The variable inflation is able to moderate Jakarta Islamic index, but can’t moderate variable exchange rate and Indonesia sharia bank certificate on the growth of Islamic mutual funds.